Elucidating clinical phenotypic variability associated with the polyT tract and TG repeats in CFTR. Issue 9 (10th July 2021) - Nykamp, Keith; Truty, Rebecca; Riethmaier, Darlene; Wilkinson, Julia; Bristow, Sara L.; Aguilar, Sienna; Neitzel, Dana; Faulkner, Nicole; Aradhya, Swaroop
Abstract: Biallelic pathogenic variants in CFTR manifest as cystic fibrosis (CF) or other CFTR‐related disorders (CFTR‐RDs). The 5T allele, causing alternative splicing and reduced protein activity, is modulated by the adjacent TG repeat element, though previous data have been limited to small, selective cohorts. Here, the risk and spectrum of phenotypes associated with the CFTR TG‐T5 haplotype variants (TG11T5, TG12T5, and TG13T5) in the absence of the p.Arg117His variant are evaluated. Individuals who received physician‐ordered next‐generation sequencing of CFTR were included. TG[11‐13]T5 variant frequencies (biallelic or with another CF‐causing variant [CFvar]) were calculated. Clinical information reported by the ordering provider or the individual was examined. Among 548, 300 individuals, the T5 minor allele frequency (MAF) was 4.2% (TG repeat distribution: TG11 = 68.1%, TG12 = 29.5%, TG13 = 2.4%). When present with a CFvar, each TG[11‐13]T5 variant was significantly enriched in individuals with a high suspicion of CF or CFTR‐RD (personal/family history of CF/CFTR‐RD) compared to those with a low suspicion for CF or CFTR‐RD (hereditary cancer screening, CFTR not requisitioned). Compared to CFvar/CFvar individuals, those with TG[11‐13]T5/CFvar generally had single‐organ involvement, milder symptoms, variable expressivity, and reduced penetrance. These data improve our understanding of disease risks associated with TG[11‐13]T5 variants and have important implications for reproductive genetic counseling.